2023
DOI: 10.1021/acs.est.2c09223
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence and Cooperation between Comammox and Anammox Bacteria in a Full-Scale Attached Growth Municipal Wastewater Treatment Process

Abstract: Cooperation between comammox and anammox bacteria for nitrogen removal has been recently reported in laboratory-scale systems, including synthetic community constructs; however, there are no reports of full-scale municipal wastewater treatment systems with such cooperation. Here, we report intrinsic and extant kinetics as well as genome-resolved community characterization of a full-scale integrated fixed film activated sludge (IFAS) system where comammox and anammox bacteria co-occur and appear to drive nitrog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 59 publications
8
36
1
Order By: Relevance
“…CAOB activity increased with higher DO concentrations, with apparent oxygen affinity constant of K O = 0.62 mg/L in the study (Figure b). This was consistent with previous studies. , Vilardi et al found that comammox-dominated nitrification activity was similar at DO between 2 and 4 mg/L, which increased by about 70% at 6 mg/L . Zhao et al demonstrated ammonia oxidation rates increased at DO from 2 to 6 mg/L in a comammox-enriched MBBR, attributed to the relatively low apparent oxygen affinity constant of Ca.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…CAOB activity increased with higher DO concentrations, with apparent oxygen affinity constant of K O = 0.62 mg/L in the study (Figure b). This was consistent with previous studies. , Vilardi et al found that comammox-dominated nitrification activity was similar at DO between 2 and 4 mg/L, which increased by about 70% at 6 mg/L . Zhao et al demonstrated ammonia oxidation rates increased at DO from 2 to 6 mg/L in a comammox-enriched MBBR, attributed to the relatively low apparent oxygen affinity constant of Ca.…”
Section: Resultssupporting
confidence: 91%
“…The co-occurrence and cooperation of CAOB and AnAOB was recently demonstrated in lab-scale and full-scale nitrogen removal reactors in attached growth modes. 16,17,19,21 The CAOB-AnAOB synergy could be largely regulated by oxygen, which was further investigated by microrespirometry tests under NH 4 + -unlimited (residual NH 4 + > 1 mg N/L) and varied DO (0−2 mg/L) conditions. Nitrification activity was positively correlated with the DO (Figure 4b).…”
Section: Total Nitrogen Removalmentioning
confidence: 99%
“…AOB are long thought to be exclusively responsible for ammonia oxidization, however, increasing evidence showed that AOA and comammox bacteria (an oxidizer by which the conversion of ammonium to nitrate can be achieved solely) are two other major AOMs responsible for ammonia oxidation. ,, Previously, owing to the high ammonia and oxygen affinity, it was believed that the AOA and comammox bacteria likely contribute to the nitrogen conversion in oligotrophic ecosystems with limited ammonium and oxygen, such as in drinking water treatment, estuaries. and freshwater settings. , Recent studies have shown that these novel AOMs can also be enriched and play an important role in nitrogen turnover of ammonium-sufficient wastewater ecosystems, where the ammonium concentration is at orders of magnitude above geochemical ecosystems. Nowadays, novel AOMs have been deemed as an attractive alternative to AOB in WWTPs for sustaining ammonia oxidization under stressful conditions, e.g., low temperature (10–20 °C) , and low DO (<1.0 mg/L), , and have exhibited advantages of maintaining the stability of a microbial community, saving energy consumption and reducing GHG emissions. , …”
Section: Mainstream Nitrite Supply Driven By Novel Aoms and Nitrate R...mentioning
confidence: 99%
“…Comammox bacteria are ubiquitous in natural and engineered systems, , and was first detected in a full-scale WWTP in 2016, expanding our knowledge of the biological nitrogen transformations in wastewater treatment. Comammox has a great significance for WWTPs retrofit that it provides an attractive collaboration paradigm with anammox, exhibiting remarkable benefits in saving aeration, organics consumption, and sludge production. ,, Comammox Nitrospira shows a higher ammonium affinity ( K m,NH3 = 0.040–0.049 μmol/L) than AOB ( K m,NH3 = 0.01–33.3 μmol/L) (Table ), suggesting that comammox can occur in an activated sludge system and contribute to a better effluent quality in WWTPs. , Although the exact oxygen affinity of comammox bacteria is still unclear, all the theoretical predictions, genomic studies, and laboratory studies have shown that they are likely adapted to environments with low DO concentrations (0.05–1.0 mg/L). ,, For instance, comammox Nitrospira accounted for 4% of the overall microorganisms in a lab-scale mainstream nitrification reactor (400 days) with a DO concentration of 0.2–1.0 mg/L, while the relative abundance of AOB was less than 1% . Despite our rapidly evolving knowledge of favorable conditions for comammox bacteria, very little is known about their diversity in ecophysiology and habitat preferences. , The nitrite affinity of comammox bacteria varies in a wide range.…”
Section: Mainstream Nitrite Supply Driven By Novel Aoms and Nitrate R...mentioning
confidence: 99%
See 1 more Smart Citation